Pro-Poor Land Reform: A Critique - Remollino, Alexander Martin (Kasarinlan: Philippine Journal of Third World Studies; Vol 24 No 1-2 (2009): The Philippines in the WTO, 2011)
Land reform is an issue that has recurred throughout human history: one that has often shown the power to make or unmake nation-states and one that has repeatedly sparked uprisings of various types—including national revolutions.